2017
DOI: 10.5935/abc.20170125
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacity in Congenital Heart Disease: A Systematic Review and Meta-Analysis

Abstract: BackgroundChildren and adolescents with congenital heart disease often have alterations in their exercise capacity that can be evaluated by various functional testing.ObjectiveTo evaluate the functional capacity of children and adolescents with congenital heart disease (CHD) with systematic review and meta-analyses.MethodsThe review included observational studies, data from the first evaluation of randomized clinical trials or observational follow-up periods after clinical trials which evaluated functional cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
13
0
5
Order By: Relevance
“…One of the factors that determine the level of PA has to do with the social environment and the influence that the family has on children. 43 In the case of children with CHD, in addition to the limitation in physical capacity due to the heart defect, 13 the social restriction is even greater and probably maximised by the parents. 44 Several authors showed that the restriction for the development of PA has to do with aspects surrounding cardiac dysfunction, such as the restrictive attitude of the family limiting the ability of follow the recommendations of the cardiologist, 22,28 and the self-efficacy that the child perceives of his/her own ability to perform PA. 27 The severity of CHD is another aspect to consider within the determinants of PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the factors that determine the level of PA has to do with the social environment and the influence that the family has on children. 43 In the case of children with CHD, in addition to the limitation in physical capacity due to the heart defect, 13 the social restriction is even greater and probably maximised by the parents. 44 Several authors showed that the restriction for the development of PA has to do with aspects surrounding cardiac dysfunction, such as the restrictive attitude of the family limiting the ability of follow the recommendations of the cardiologist, 22,28 and the self-efficacy that the child perceives of his/her own ability to perform PA. 27 The severity of CHD is another aspect to consider within the determinants of PA.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that physical capacity, understood as the maximum physical effort that a subject can perform, and PA are determinants of morbidity and mortality in adults with CHD 8,11,12 and, in children with CHD it is significantly lower in comparison with healthy controls, 13,14 it has been stated that MVPA is the variable that has a direct relationship with increases in self‐reported HRQOL 15,16 . Several studies have described the impact of CHD on PA in children, reporting the risk of suffering other cardiovascular and metabolic diseases during adolescence 4,7,17,18 and adulthood 8,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these children face restricted physical activity and lower exercise capacity. [ 20 ] Thus, families tried to supervise their children's activities to prevent fatigue and dyspnea, and teach them about it. In a similar study, parents tried to prevent activities which increased the heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, swollen coronary sinusoids have been detected in children with pulmonary atresia 4,5 and patients with d-transposition of the great arteries and tetralogy of Fallot have reduced myocardial perfusion via the microvasculature 6 . Patients with CHDs often have reduced exercise tolerance, which could point toward microvascular defects 7 . However, expansion in our understanding of microvascular heart development and its role in heart disease requires new tools and a quantitative approach.…”
mentioning
confidence: 99%